Monetary Policy and Macroprudential Policy: Rivals or Teammates? - Simona Malovana; Jan Frait (Charles University in Prague, Institute of Economic Studies (IES), 2016)
This paper sheds some light on situations in which monetary and macroprudential policies may interact (and potentially get into conflict) and contributes to the discussion about the coordination of those policies. Using data for the Czech Republic and five euro area countries we show that monetary tightening has a negative impact on the credit-to-GDP ratio and the non-risk-weighted bank capital ratio (i.e. a positive impact on bank leverage), while these effects have strengthened considerably since mid-2011. This supports the view that accommodative monetary policy contributes to a build-up of financial vulnerabilities, i.e. it boosts the credit cycle. On the other hand, the effect of the higher bank capital ratio is associated with some degree of uncertainty. For these and other reasons, coordination of the two policies is necessary to avoid an undesirable policy mix preventing effective achievement of the main objectives in the two policy areas.
Keywords: E52; E58; E61; G12; G18; 330; Bayesian estimation; financial stability; macroprudential policy; monetary policy; time-varying panel VAR model